The iDMZ "Sayaw Pinoy!" Business Plan - Demetillo, Mary Rose Juanson (University of the Philippines Diliman, 2012)
The advent of internet technology provided a new medium for radio broadcasting. Internet radio industry all over the world is growing and the local scene is likewise keeping up with this growth. Aside from terrestrial radio stations that rebroadcast or simultaneously broadcast their programs over the net, there are also stations that broadcast their programs solely via the Internet. These "internet-only" radio stations in the Philippines totaled to 54 according to shoutcast.com (2011). iDMZ "Sayaw Pinoy!" is an internet radio station inspired by the icon radio station in the 80s known as 89 DMZ (Dance Music Zone). The iDMZ "Sayaw Pinoy!", was formally launched last August 28, 2011 and is currently airing over www.89dmz.com. The company was registered under the said domain name on November of 2010. It was conceptualized by two former members of 89 DMZ - a disc jockey (DJ) and a member of the mobile circuit. It is the first and the only Filipino interactive website that offers non-stop dance music in form of song mixes that caters to entire genre, from the 70s up to the present. Prior to the launching of DMZ "Sayaw Pinoy!," the founder has created an open-group page in Facebook under the account "89 DMZ (Dance Music Zone)". To date, the page has approximately 3,000 members from around the world and the iDMZ Sayaw Pinoy! website "hits" ("likes") were close to 10,000. The company's vision is "to be known globally as the first internet dance music radio station in the Philippines". Its mission are : to provide unadulterated dance music, catering song hits from the 70s up to the present. - to reach out to listeners all over the world through modern web technology, - to serve as a medium and a creative avenue for entertaining music savvy listeners and connecting them through the internet technology. Through the computer and internet technology music and radio industry has evolved in terms of accessibility and innovativeness. It provided ease of access with the various platforms that can support radio broadcasting. The social networking site, Facebook became a venue that reflected the market demand for online radio programming of various dance music. This recent shift of Philippine terrestrial radios from niche programming to the trendy mass-based programming has left the former (to include dance music lovers) detached with the terrestrial radios and went online to catch the songs that they prefer. This opportunity was seen by the founder to start an internet-based radio that will cater to the niche market of dance music lovers. The market was properly screened prior to the launching of the business through a social networking site. The owner scouted for the best talents from his colleagues and family members to help him plan, launch and operate the business.